UPAYA MENINGKATKAN EMPLOYEE ENGAGEMENT BEHAVIOR PETUGAS PELAYANAN INFORMASI BANDAR UDARA I GUSTI NGURAH RAI - Purnama Sari, Desak Made Febri; Putri, Dita Arnita (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Transportation at this time is growing rapidly, the use of airplanes has become a promising option for many people. This causes a lot of flight traffic that occurs in all airports. Because there are so many processes that must be gone through to bring in and dispatch passengers, of course, officers or employees who are qualified and competent in their respective fields are needed. Thus, efforts to improve employee engagement behavior will be needed to reduce the risk of employee resignation or turnover. The implementation of this activity aims to improve employee engagement behavior among land side and airport terminal information service employees. By increasing employee engagement behavior among information service officers, it is hoped that loyalty, quality and a sense of comfort when working or on duty will increase. This activity is carried out by conducting discussions with the officer concerned. Discussions and assistance must continue to be carried out in the future so that employees can convey the problems they face, to get solutions.